Evaluating long-term outcomes of left atrial appendage occlusion: the results of a prospective single-center registry. (24th May 2021) - Maarse, M; Wintgens, L; Aarnink, E; Huijboom, M; Abeln, B; Klaver, M; Staal, D; Rensing, B; Van Dijk, V; Swaans, M; Boersma, L
Abstract: Funding Acknowledgements: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): This work was supported by an unrestricted grant from Boston Scientific. Boston Scientific was not involved in the design/conduct of the study, data collection/analysis and interpretation of the data and preparation of the manuscript. Background Percutaneous left atrial appendage occlusion is an emerging alternative to anticoagulation in the prevention for stroke in patients with atrial fibrillation, especially in patients with a contra-indication for oral anticoagulation therapy. Long-term results on the efficacy and safety of this treatment remain scarce. Methods In this single-center prospective registry, data of all consecutive patients that underwent percutaneous left atrial appendage closure between 2009 and 2019 were collected. Patients with successful left atrial appendage closure (peri-device leakage ≤5mm) and at least one year of follow-up data were analyzed. The occurrence of thrombo-embolic events (ischemic stroke, TIA and systemic embolism), major bleeding events (BARC >2) and anticoagulation use during long-term follow-up were evaluated. Results A total of 192 patients after left atrial appendage occlusion were included (61 % male, age 69.0 ± 8.4 years, CHA2DS2-VASc 4.0[3.0-5.0], HAS-BLED 3.0[2.0-3.25]) with a mean follow-up duration of 5.7 ± 2.8 years (in total 1087 patient-years). During follow-up 36 patients (19%) died. 49 thrombo-embolic complications were observed in 38 patients. The ischemic stroke rate was 1.9 events per 100 patient-years, accounting for a 70% reduction compared to CHA2DS2-VASc predicted rate. Device-related thrombus (DRT) occurred in 5 patients (2.6%), 3 were observed during routine follow-up and were not associated with thrombo-embolic complications. The other 2 DRT were observed in patients presenting with ischemic stroke more than 3 years after device implantation. Furthermore, 38 non-procedural major bleeding complications occurred in 19 patients, resulting in 3.5 events per 100-patients years, accounting for a reduction of 43% compared to estimated bleeding rates under OAC use. At the end of the study 71% of all patients were on single antiplatelet or no antiplatelet/anticoagulation treatment at all. Conclusions During long-term follow-up thrombo-embolic event rates and non-procedural major bleeding rates were consistently low (ischemic stroke rate reduction 70% and non-procedural major bleeding rate reduction 40% compared to predicted rates). These results confirm the efficacy of left atrial appendage occlusion.